THE PREBIOTIC INFLUENCE OF INULIN ON GROWTH RATE AND ANTIBIOTIC SENSITIVITY OF Lactobacillus casei - DEBOLINA BANERJEE; RANJANA CHOWDHURY; PINAKI BHATTACHARYA (Innovare Journal of Engineering and Technology, 2016)
Objective: This research study is focused on the prebiotic effect of inulin on the antibiotic sensitivity of probiotic Lactobacillus casei and on the determination of functionality of specific growth rate (µ) of the probiotic bacteria on the concentrations of lactose (CL= 10-30g/L) and inulin (CI = 0.164-0.625g/L) along with the optimization of growth condition through Response Surface Methodology. Methods: The sensitivity of Lactobacillus casei towards norfloxacin was determined using well diffusion method. Using the initial values of µ (h-1) of Lactobacillus casei at different values of CL(g/L) and CI (g/L), the functionality of µ on the concentrations of the carbon sources have been derived and optimum condition has been identified. Results: Although L.casei is sensitive to norfloxacin, resistance is developed in presence of inulin. Quadratic model equation µ =0.83+0.054 * CL -0.035* CI -0.049* CL * CI -0.29* CL 2 -0.33* CI 2 is valid and the optimum value of specific growth rate is 0.8285h-1 at CL=20g/L and CI =0.32g/L. Conclusion: The interesting observation of development of antibiotic resistance of L.casei in presence of inulin suggests that the intake of probiotic L casei, may be done along with prebiotic inulin when a patient is treated with antibiotics like norfloxacin. Moreover the model equation correlating the functionality of growth rate of L.casei on lactose and inulin will be helpful in fortifying the probiotic milk products and drugs with prebiotics like inulin.